Learning to support science: gender differences in how scientific literacy mediates formal education’s effect on U.S. adults’ public support for science - Roessger, Kevin Mark; Greenleaf, Arie Todd (Frontiers in Education, 2025)
IntroductionScientific literacy is targeted by the knowledge deficit model, which predicts that increased scientific literacy improves public support for science. The model, in part, assumes formal education drives scientific knowledge, which, in turn, drives support for science. To date, though, this relationship is unclear, and research shows that, while formal education is associated with adults’ public support for science, scientific literacy maintains only a small relationship with support for science, one that may differ by gender.MethodsUsing a conditional process analysis, we drew on 2018 General Social Survey data to examine whether scientific literacy mediates education’s effects on support for science and whether this relationship differs by gender.ResultsWe found that scientific literacy partially mediates the effect of formal education on public support for science: As formal education increases, so does scientific literacy, which in turn increases support for science. This relationship differed markedly by gender. For men, education improved support for science only through scientific literacy gains, whereas for women, education improved support for science regardless of scientific literacy.DiscussionOur findings demonstrate a key assumption of the knowledge deficit model, namely that, overall, more education leads to more scientific literacy, which in turn leads to greater public support for science. Considered alone, though, these findings ignore substantial gender differences. Specifically, the mediational process assumed by the knowledge deficit model occurred only in men. It was an inaccurate account of formal education’s effect in women. This may be a principal reason why the knowledge deficit model is roundly criticized as inadequate for addressing public communication of science.